TRANSINTERNALISASI BUDAYA PENDIDIKAN ISLAM: MEMBANGUN NILAI ETIKA SOSIAL DALAM PENGEMBANGAN MASYARAKAT - Imam Mawardi (Hunafa: Jurnal Studia Islamika, 2011)
Abstract: Islamic education is a conservationist  and  connector for  socio-ethical values of society.  Therefore, the  paradigm which should be established  is  how to  adapt Islamic education with social changes  based on the modernity with  moral  values as outlined in the teachings of Islam.  With  social  ethics, Islamic  education  can became a bridge for  the global issues  in all aspects of community  culture, beginning from family  to   the larger and more complicated communities. Hence. the system of Islamic education which  should be actualized   is that related to  interdisciplinary,  multi-disciplinary  and  transdisciplinary subject  with  the policy of mutual binding between the compliance of socio-religio cultural  values and  the needs of the market.Kata Kunci: transinternalisasi, pendidikan Islam, etika sosial, masyarakat